A Review of Viscosity Measurement Techniques for Semi-Solid Metal Fluids in Thixoforming Processes - Megalingam, A; Asnul Hadi, Ahmad; Nasrul Azuan, Alang; N., Muhammad; Muduli, K. (Universiti Malaysia Pahang, 2024)
This paper critically reviews two viscometry techniques: capillary viscometers and parallel plate compression (PPC) viscometers, which are used in the viscosity measurement of semi-solid metal (SSM) fluids for thixo routes. Capillary and PPC viscometers have emerged as valuable viscometers in the study of thixo routes of SSM, with insights into their unique flow behavior being explored. Thixoprocessing of SSM is particularly suitable for specific alloys, especially those with specific solidification properties such as eutectics. It is a method of thixoforming that uses a material's non-dendritic microstructure. The thixo method's viscosity measurement is challenging, requiring sample preparation, sophisticated equipment, precise temperature, and pressure control. Previous studies have lacked sufficient information on measurement methods, viscometers, and limitations to measuring viscosity for the thixo route of SSM. Hence, this study thoroughly examines the principles, advantages, limitations, and application areas of viscometry methods. Several factors influencing viscosity measurements, such as temperature, shear rate, and sample preparation, are discussed in detail. A comparative analysis is conducted to evaluate the performance and accuracy of capillary viscometers and parallel plate compression viscometers. This review will provide a comprehensive understanding of SSM's viscometry techniques and assist researchers and practitioners in selecting the most appropriate method for their specific applications in semi-solid metal processing and characterization.